A minha prática pedagógica em uma nova perspectiva - MONTEIRO, Lemaire Regina da Silveira Cardoso (2024)
This work is about an autobiography,from childhood to the Pedagogy course by the Federal University of Pará – UFPA/PARFOR, doing a reflection and analysis about my practice pedagogy. aims to bring information about my life trajectory, articulated with my pedagogical practice in school and society . The questions that guided this work were : in what way i was teaching ? What are the contributions of the Pedagogy course to my professional life? Why graduate teachers still use a single method? What are the contributions of the formations to the teaching practices? The pedagogical practice is related to the level of teacher instruction and the capacity for innovation it has. In summary, this work will identify the need continuing education for teachers. To write, in full maturity, the memorial means to identify a concrete and safe phase of my professional and personal life; i wrote situations that I thought were the most significant.